1989
DOI: 10.1177/00315125890693-256
|View full text |Cite
|
Sign up to set email alerts
|

Helping Orientations: Four Dimensions,

Abstract: The underlying factor structure of four helping and coping orientations was investigated. The four orientations are the foundations of four models of helping and coping. Each model consists of a person's orientations toward helping behavior and the set of likely factors and behaviors related to the orientations. The orientations are believed to influence how a person interacts with others in a helping situation and how that person attempts to help himself (cope). Factor analysis in two studies supports the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A 2-week test-retest reliability has been estimated at.86 for the Cause Scale and at.70 for the Solution Scale (Bailey & Hayes, 1998). McCracken, Hayes, and Dell (1997) demonstrated concurrent validity evidence by showing that the Cause and Solution scales correlated in positive predicted directions with the Derived Cause and Derived Solution scales of the Helping Coping Orientation Measure (Michlitsch & Frankel, 1989). Construct validity evidence has been provided by Hayes and Wall (1998), who demonstrated that clinicians rated clients diagnosed with posttraumatic stress disorder as significantly less responsible for the cause of and solution to a problem in comparison to clients diagnosed with bulimia.…”
Section: Methodsmentioning
confidence: 99%
“…A 2-week test-retest reliability has been estimated at.86 for the Cause Scale and at.70 for the Solution Scale (Bailey & Hayes, 1998). McCracken, Hayes, and Dell (1997) demonstrated concurrent validity evidence by showing that the Cause and Solution scales correlated in positive predicted directions with the Derived Cause and Derived Solution scales of the Helping Coping Orientation Measure (Michlitsch & Frankel, 1989). Construct validity evidence has been provided by Hayes and Wall (1998), who demonstrated that clinicians rated clients diagnosed with posttraumatic stress disorder as significantly less responsible for the cause of and solution to a problem in comparison to clients diagnosed with bulimia.…”
Section: Methodsmentioning
confidence: 99%
“…For example, do their conceptions of the world as just or unjust change? See Bnngle and Velo (1996) and Michlitsch and Frankel (1989).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Models of helping and coping offer insight into assignments of responsibility for problems and solutions. Research by Michlitsh and Frankel (1989) indicates that "when people help themselves or others, the direction of behavior is influenced by fundamental beliefs about blame and control" (p. 1371). As such, models of helping and coping can help us understand the authors' implicit attributions for responsibility, acknowledge any limitations in this orientation, and open a new area of exploration with regards to developing interventions aimed at reducing the incidence of STD among Mexican migrants.…”
Section: Discussionmentioning
confidence: 99%